Gambaran Pengetahuan, Sikap, dan Perilaku Kebiasaan Makan pada Orang Sehat dan Pradiabetes di Kabupaten Bengkayang, Kalimantan Barat - Agustina, Venti; Triandhini, R.L.N.K. Retno; Ng, Agustina (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Before diabetes mellitus occurs, it is preceded by the occurrence of prediabetes. Prediabetes is a condition where blood sugar levels are above normal or elevated in the blood, but has not yet entered the stage of diagnosis of Diabetes Mellitus. The high increase in the number of cases of prediabetes to DM is related to changes in people's lifestyle behavior and environmental factors. The most prominent factor is an unbalanced diet that triggers risk factors for prediabetes and if not managed properly will lead to DM.Methods: This type of research is quantitative with a cross sectional design. The study was conducted in the Capkala Health Center Work Area in September-December 2020, the research respondents amounted to 62 people which were divided into 31 healthy people and 31 with prediabetes. Data collection techniques in the form of knowledge questionnaires, attitudes and behavior of eating habits and clinical examination consisting of fasting blood sugar (GDP), systolic and diastolic blood pressure, and total cholesterolResults: The results showed that 96.8% of prediabetic respondents had good knowledge of eating habits and 100% of those who were healthy. Respondents who have a positive attitude towards efforts to eat habits are 100%. Prediabetic respondents who have good behavior towards habits 90.3% and 100% healthy.Conclusion: The conclusion of this study is that the knowledge, attitudes, and behavior of eating habits in healthy and prediabetic people are in the good category.